The New Rules of Green Marketing and Its Role in Guiding Clients Towards Green Purchasing Behavior (Exploratory Study in Light of Go Green Syria) - بلدية, إياد (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study will study the modern rules of green marketing and its role in guiding customer toward purchasing behavior in light of go Green Syria. To explore the most influential Motives in the green behavior of customers and the extent of their response with the philosophy and the concept of green marketing and the extent of their awareness of environmental issues. To achieve the objectives of the study, three main hypotheses were formulated, The researcher used the Statistical Package for Social Sciences SPSS V (23) to test hypotheses, and reached several conclusions, including: Modern rules of green marketing orients Respondents' Green purchasing behavior well for motives that are related to the performance of green product and the green product production, and is acceptable for motives related to the entrance of the life cycle of greening, and poorly for motives related to green price. Based on the results of the study, Researcher suggested the need to disseminate the concepts and philosophy of green life and green marketing and environmental awareness, to convert Syrian consumer to green consumer in order to ensure the success of Go Green Syria.